2015
DOI: 10.1530/rep-15-0226
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling represses GATA4-induced expression of genes involved in steroid biosynthesis

Abstract: Notch2 and Notch3 and genes of the Notch signaling network are dynamically expressed in developing follicles, where they are essential for granulosa cell proliferation and meiotic maturation. Notch receptors, ligands, and downstream effector genes are also expressed in testicular Leydig cells, predicting a potential role in regulating steroidogenesis. In this study, we sought to determine if Notch signaling in small follicles regulates the proliferation response of granulosa cells to follicle stimulating hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 101 publications
(173 reference statements)
2
14
1
Order By: Relevance
“…Specifically, NOTCH2 is expressed in all GCs of small growing follicles and Notch signaling induces the proliferation of many cell types, including GCs . Notch signaling could repress steroid synthesis in small preantral follicles and MA‐10 Leydig cells . Our finding agrees with that in previous reports; we found that NOTCH2 could be downregulated by melatonin and repress estradiol synthesis in pig GCs.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, NOTCH2 is expressed in all GCs of small growing follicles and Notch signaling induces the proliferation of many cell types, including GCs . Notch signaling could repress steroid synthesis in small preantral follicles and MA‐10 Leydig cells . Our finding agrees with that in previous reports; we found that NOTCH2 could be downregulated by melatonin and repress estradiol synthesis in pig GCs.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to the findings above, transfection of a gonadotropin-responsive mouse cell line with NICD1 or NICD2 , leads to a decrease in progesterone production, implying that Notch activation normally functions to suppress steroidogenesis (George et al 2015). In addition, the expression of StAR , Cyp19a1 , and HSD3b1 are significantly upregulated following pharmacological suppression of Notch signaling in cultured preantral follicles and downregulated with transient transfection of NICD1-3 .…”
Section: Notch Signaling During Luteinizationcontrasting
confidence: 67%
“…In addition, the expression of StAR , Cyp19a1 , and HSD3b1 are significantly upregulated following pharmacological suppression of Notch signaling in cultured preantral follicles and downregulated with transient transfection of NICD1-3 . Furthermore, activation of the Notch pathway represses the ability of GATA4 to induce the expression of these genes through Notch target gene expression and promoter binding, rather than through dimerization of Notch target genes with GATA4 (Figure 3C) (George et al 2015). These findings, together with studies employing DLL4 and γ-secretase inhibitors discussed above, indicate that alteration in the levels of basal Notch activity negatively impact progesterone production in steroidogenically active cells, suggesting complex regulatory effects of steroid hormone production by Notch signaling.…”
Section: Notch Signaling During Luteinizationmentioning
confidence: 99%
“…The NOTCH system (ligands, receptors, and target genes) is expressed in the ovaries in different structures, such as oocytes, primary, secondary and antral follicles, corpora lutea, theca cells, ovarian surface epithelium, and vasculature (Vanorny & Mayo, and references therein). Various critical roles have been defined for NOTCH factors in ovary biology, such as follicle formation and growth, meiotic maturation, vasculogenesis, and hormone synthesis (George, Hahn, Rawls, Viger, & Wilson‐Rawls, ; Trombly, Woodruff, & Mayo, ; Vanorny & Mayo, ; Xu & Gridley, ). These findings support proposing NOTCH2 as a coherent candidate gene related to POI's etiology.…”
mentioning
confidence: 99%